2020
DOI: 10.1080/23311932.2020.1746229
|View full text |Cite
|
Sign up to set email alerts
|

Participatory variety selection and stability analysis of Durum wheat varieties (Triticum durum Desf.) in northwest Amhara

Abstract: Citation informationCite this article as: Participatory variety selection and stability analysis of Durum wheat varieties (Triticum durum Desf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The main effects of genotype, environment and G × E interaction were very significant (P < 0.001) (Table 6). The magnitude of the SSGE was 3.59 times more than that for genotype effect, demonstrating there were considerable deferential response among the genotypes to change of environment and the differential discriminating ability of the test environment (Shukla et al 2015;Heidari et al 2017;Bavandpori et al 2018;Tekdal & Kendal 2018;Mekonnen et al 2020). The value of the GEI is mostly due to variations in environmental conditions from supplementary irrigated to rainfed and from year to year.…”
Section: Ammi Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…The main effects of genotype, environment and G × E interaction were very significant (P < 0.001) (Table 6). The magnitude of the SSGE was 3.59 times more than that for genotype effect, demonstrating there were considerable deferential response among the genotypes to change of environment and the differential discriminating ability of the test environment (Shukla et al 2015;Heidari et al 2017;Bavandpori et al 2018;Tekdal & Kendal 2018;Mekonnen et al 2020). The value of the GEI is mostly due to variations in environmental conditions from supplementary irrigated to rainfed and from year to year.…”
Section: Ammi Analysismentioning
confidence: 97%
“…The AMMI model by puncturing genotypes and environments on the biplot, identifies the position of the genotypes relative to each other and the studied environments (Elakhdar et al 2017). Mohammadi et al (2015), Ajay et al (2020), Khan et al (2020), Lozada & Carter (2020), Mekonnen et al (2020), Mohammadi et al (2020) and Verma & Singh (2021) by examining the stability of wheat genotypes reported that the AMMI method with high fitting power, is more suitable than other methods for determining genotypes with general and specific adaptability for different locations. Ahakpaz et al (2021) by examining 18 rainfed barley genotypes for three cropping years in cold rainfed regions of Iran, reported that the effects of G, E and GEI on grain yield were significant.…”
Section: Introductionmentioning
confidence: 99%
“…Pigmented barley ( Hordeum vulgare ) and wheat ( Triticum aestivum and Triticum turgidum ) are gaining attention due to their rich phenolic content, health implications and various food applications [ 8 , 9 , 10 , 11 , 12 , 13 ]. Hordeum vulgare is a common hull-less barley that is used in making beverages and other cereal based products [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, pigmented varieties of the common bread wheat ( Triticum aestivum ) offer great nutritional value due to phenolic content [ 8 ]. The blue coloured variety is pigmented in the aleurone layer and has been the subject of studies focused on the antioxidant activity of pigmented wheats and selective breeding of new varieties [ 11 , 12 ]. On the other hand, Triticum turgidum is a durum wheat originating from Ethiopia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation